EFFECTIVENESS OF CRIMINAL SANCTIONS FOR VIOLATORS OF SMOKE-FREE AREAS IN INDONESIA: CHALLENGES AND RESPONSIVE LAW SOLUTIONS - Darma, I Made Wirya; Mahadnyani, Tjokorda Mirah Ary (Universitas Syiah Kuala, 2024)
Cigarettes pose a significant global health threat, resulting in millions of related deaths annually. Consequently, governments worldwide, including Indonesia, have implemented smoke-free area policies in an effort to mitigate these health concerns. This study analyzes the effectiveness of criminal sanctions imposed on violators of smoke-free areas in Indonesia, while identifying legal challenges in enforcing these regulations and proposing normative solutions within the framework of responsive law. Utilizing a normative legal approach, this study combines both statutory and conceptual methodologies to analyze primary, secondary, and tertiary legal materials through literature studies. It employs a qualitative descriptive analysis method to examine the efficacy of criminal sanctions against violators of smoke-free areas in the context of responsive law. The results indicate that the effectiveness of criminal sanctions to enforce smoke-free areas in Indonesia is hindered by various constraints, including weak law enforcement, limited public awareness, economic conflicts of interest, and inadequate smoking facilities. This study recommends adopting a responsive law approach. This entails strengthening law enforcement, conducting continuous socialization and education programs, establishing special smoking facilities, involving the tobacco industry in health policy-making, and reformulating policies through a participatory approach. By implementing these responsive law solutions, it is anticipated that smoke-free area regulations can be more effectively enforced, garner the support of all parties involved, and contribute to enhanced public health protection from the risks associated with cigarette smoke.